Achievement of control of bronchial asthma at the stage of medical rehabilitation - Grygus I.M (Kharkov National Pedagogical University, 2011)
An inspection is conducted 70 patients on intermittent bronchial asthma at the stage of intensifying. The special program of medical rehabilitation, which includes the modified methods of medical physical culture, physical therapy facilities, is offered in permanent establishment. Application of this program brought to the height of size of Asthma Control Test from 17,41±0,35 to 24,03±0,32 points over. Control of flow of disease which did not come at treatment of patients only by medicinal preparations was arrived at in all cases of application of the program of medical rehabilitation.